Cooperative NOMA system with incremental relaying over Nakagami- fading channels - Zhenling Wang; Dawei Qiao (International Journal of Distributed Sensor Networks, 2022)
In our article, we apply incremental relay to the cooperative non-orthogonal multiple access network, in which the incremental relay employs amplify and forward protocol. The main communication process of the system is that one base station transmits messages to multiple non-orthogonal multiple access users with the assistance of incremental relay. In addition, we deeply analyze the outage behavior of the incremental cooperative non-orthogonal multiple access system over Nakagami- m fading channels. Specifically, the exact and asymptotic closed-form expressions of outage probabilities are all derived for paired users u n and u f , which are nearby and distant user, respectively. On this basis, the diversity orders of the paired users u n and u f are also acquired, which are μ ( n + f +1) and μ( f +1). We also investigate the conventional cooperative non-orthogonal multiple access system, which serves as a benchmark of the incremental cooperative non-orthogonal network. Through the proof, we can conclude that the outage behavior of the distant u f has been improved by adopting incremental relay. Finally, the performance of the system is simulated. The following conclusions can be drawn from the numerical simulation results: (1) the outage performance and throughput of the system have been significantly improved by using the incremental relay protocol; (2) as the multipath fading μ increases, the outage performance of the system becomes better; and (3) the greater the difference in channel gain between paired users, the incremental cooperative non-orthogonal system can achieve better outage performance.